Characteristics and Opportunistic Infections of AIDS Patients in East Java Province in 2018 - Gracia Satyawestri Pribadi; A.B. Firman Cahyono (Jurnal Berkala Epidemiologi, 2021)
Background: Acquired immunodeficiency syndrome (AIDS) is a health problem in East Java. Opportunistic infections are one of the causes of morbidity and mortality in patients with human immunodeficiency virus (HIV) and AIDS in Indonesia. Purpose: This study aimed to describe the characteristics and opportunistic infections of AIDS patients in East Java Province, 2018. Methods: This study was conducted as observational descriptive research, and a survey was used as the research design. The research location was in East Java Provincial Health Office, and the study was carried out in August 2019. We used secondary data taken from the results of surveillance of AIDS patients in 2018. The sampling method of the study was total sampling, with 1,138 AIDS patients. The variables studied included the patients’ characteristics (sex, age, type of work, and risk factors) as well as the number and types of opportunistic infections. Results: The majority of the AIDS patients in East Java in this sample were male (70.74%), belonged to the adults (26–45 years old) group (62.65%), and worked as employees/laborers (46.08%). In terms of sexual orientation, the majority were heterosexuals (81.81%) or homosexuals (10.63%). The majority of patients experienced one type of opportunistic infection (46.08%), with histoplasmosis (48.77%) and tuberculosis (TB) (42.62%) as the most frequently experienced opportunistic infections. Conclusion: Characteristics that are risk factors for contracting AIDS in East Java include being male, being of adult age, working as an employee/laborer, and being heterosexual. There are also risks of opportunistic infections, particularly histoplasmosis and TB.